Pengendalian Penularan COVID-19 Melalui Penerapan Non Medical Infant Face Shield (Nomifes) - Nidia Yuniarsih; Nurul Laili Arifin; Hanifah Widiastuti; Nugroho Pratomo Ariyanto; Nurul Ulfah; Widodo Widodo; Budi Baharudin; Aulia Fajrin; Muhammad Ismail; Nur Fitria Pujo Leksonowati; Domi Kamsyah; James Siregar; Nurman Pamungkas; Sapto Wiratno Satoto; Mufti Fathonah Muvariz (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2021)
Personel Protective Equipment (PPE), as prevention to curb COVID-19 transmission which mainly via droplet, is a mandatory protocol as rising COVID-19 confirmed case. Face shield can protect face from droplet exposure. Besides health care professionals, pregnant women and newborn infants are susceptible population to exposure of SARS-CoV-2. Infant under two years is not recommended to use face mask due to breahing difficulty which can lead to mortality. Therefore, face shield is recommended for infant to give protection from virus transmission. As part of community service, Politeknik Negeri Batam produces Non Medical Infant Face Shield for infant and toddler to curb COVID-19 transmission. The program aims at community health centers (Puskesmas) of Batu Aji, Tanjung Uncang, Sekupang, and Kampong Jabi Nongsa. These partners value highly the community service program in terms of simplicity, clear working instruction, comfortability, recurring sterilization, and product quality. Moreover, high demand of face shield in Puskesmas that use face shield more than three times a day, indicates benefit of the community service in providing PPE for medical treatment at Puskesmas